Cultural Collision: The Interference of First Language Cultural Identity on Pragmatic Competence of the Target Language (GIST – Education and Learning Research Journal, 2016)
This reflective study explores a different perspective of intercultural communicative competency (ICC) by focusing on the speech acts that nonnative speakers of Spanish from diverse linguistic and cultural backgrounds find difficult to perform competently in various contexts in Colombia. This article covers a qualitative case study using interpretative phenomenological analysis to describe these foreign learners’ experiences. It aims to understand the role of their first language, culture, and identity in their use of Spanish and intercultural communication. The data was collected through interviews and reflection notes. The findings demonstrate the interaction and negotiation between the pragmatic knowledge embedded in participants’ mother tongue and the target language as they encountered contradictions of their native cultural identity and that of the target culture.
Keywords: language; culture; cultural identity; pragmatic competence; intercultural communication